2012
DOI: 10.1371/journal.pone.0044790
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Toluene Inhalation in Rats Affects White Matter Maturation with the Potential for Recovery Following Abstinence

Abstract: Inhalant misuse is common during adolescence, with ongoing chronic misuse associated with neurobiological and cognitive abnormalities. While human imaging studies consistently report white matter abnormalities among long-term inhalant users, longitudinal studies have been lacking with limited data available regarding the progressive nature of such abnormalities, including the potential for recovery following periods of sustained abstinence. We exposed adolescent male Wistar rats (postnatal day 27) to chronic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 70 publications
7
20
0
Order By: Relevance
“…Previous work has demonstrated that pathological and behavioral abnormalities are present following 8 but not 4 weeks of CIT exposure in this model (Duncan et al, 2012). Furthermore, the duration of abuse history is associated with the severity of cognitive and pathological abnormalities in human abusers (Rosenberg, Grigsby, Dreisbach, Busenbark, & Grigsby, 2002), supporting the idea of increased adverse affects with continued exposure.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Previous work has demonstrated that pathological and behavioral abnormalities are present following 8 but not 4 weeks of CIT exposure in this model (Duncan et al, 2012). Furthermore, the duration of abuse history is associated with the severity of cognitive and pathological abnormalities in human abusers (Rosenberg, Grigsby, Dreisbach, Busenbark, & Grigsby, 2002), supporting the idea of increased adverse affects with continued exposure.…”
Section: Discussionsupporting
confidence: 61%
“…Exposure to toluene inhalation was conducted as previously described (Duncan et al, 2012). Briefly, rats were acclimatized to the laboratory at least 1 h prior to exposure to toluene or air during which time their body weights were recorded.…”
Section: Toluene Inhalation Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…Rats were exposed to CIT as described [20]. Briefly, exposure was undertaken in toluene-resistant chambers (17.6 cm wide × 16.5 cm high × 16.4 cm deep; Alternative Plastics Pty Ltd., Melbourne, VIC, Australia; fittings by Swagelok, Broadmeadows, VIC, Australia) with toluene concentration maintained at 10,000 ± 100 ppm (verified by calibrated inline gas chromatography; Shimadzu Corporation, Kyoto, Japan).…”
Section: Methodsmentioning
confidence: 99%